2020
DOI: 10.1515/jbcpp-2019-0166
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of Bidens pilosa L. (Asteraceae) in a rat model of colitis

Abstract: AbstractBackgroundBidens pilosa (BP) possessed anti-inflammatory, antioxidant, and immunomodulatory activities. Its beneficial effects on intestinal inflammation and oxidative stress in 2,4,6 trinitrobenzene sulfonic acid (TNBS) induced colitis in Wistar rats was evaluated. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Our results showed that when the eight plant extracts and essential oils were mixed, the inhibitory effect of the EM on ETS invasion was more pronounced. Previous studies have shown that PGE, PAE, AAE, PMPE, POE, and AAO have hemostatic or therapeutic effects on hematochezia ( 11 , 12 , 14 17 ), and BPE, AAE, PMPE, AAO, and CSO have therapeutic or anti-inflammatory effects on enteritis ( 13 15 , 17 , 18 ). Therefore, studies exploring whether mixing the extracts and essential oils could have a synergistic effect, which better explains the observation that the EM more strongly inhibits ETS invasion than the individual extracts and essential oils, are needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that when the eight plant extracts and essential oils were mixed, the inhibitory effect of the EM on ETS invasion was more pronounced. Previous studies have shown that PGE, PAE, AAE, PMPE, POE, and AAO have hemostatic or therapeutic effects on hematochezia ( 11 , 12 , 14 17 ), and BPE, AAE, PMPE, AAO, and CSO have therapeutic or anti-inflammatory effects on enteritis ( 13 15 , 17 , 18 ). Therefore, studies exploring whether mixing the extracts and essential oils could have a synergistic effect, which better explains the observation that the EM more strongly inhibits ETS invasion than the individual extracts and essential oils, are needed.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Punica granatum L. extract (PGE) is used for deworming, to treat abdominal pain caused by worm infections, and to treat diarrhea and bleeding ( 11 ). While Plantago asiatica L. extract (PAE) can be used to treat diarrhea, dysentery, and hematuria (blood in the urine) ( 12 ), Bidens pilosa L. extract (BPE) may help treat enteritis ( 13 ), Acalypha australis L. extract (AAE) acts as an astringent hemostatic and helps treat enteritis, hematuria, and hematochezia (bloody stools) ( 14 ), and Pteris multifida Poir extract (PMPE) helps to stop bleeding and can be used to treat enteritis, hematuria, and hematochezia ( 15 ). Furthermore, Portulaca oleracea L. sp.…”
Section: Introductionmentioning
confidence: 99%
“…The alcoholic extracts inhibited the growth of Grampositive and Gram-negative bacteria [16,17,19,38]; even toward drug resistance bacteria [21], and Mycobacterium [17]; yeast, and fungi [3,16,17,19]. Other effects are also proven, including analgesic activity [18]; anti-inflammatory [3,13,14]; antioxidants [3,13,19,22]; antiplasmodial activity [3,15]; larvicidal activity [19]; haematopoietic strength and modulator of white blood cell differential count [3,12]; anticancer and antipyretic activity [3,19,20]; antiallergic activity, hypotensive effects, gastric antisecretory and antiulcer activities [3].…”
Section: Bioactive Compounds Of B Pilosa Plant Partsmentioning
confidence: 99%
“…The B. pilosa plant is widely used traditionally for treating inflammation [2]. The anti-inflammatory effect has been proven in laboratory animals of colitis [13], or induced inflamed by chemical and mechanical [80], induced gastric ulcer, liver inflammation, or arthritis-type swelling [9]. The analgesic effect of the plant was proven to reduce oral paint of HIV/AIDS patients [18].…”
Section: B Pilosa As Active Compounds In Mouthwash Formulationmentioning
confidence: 99%
See 1 more Smart Citation